Adaptability for Transitions: Components and Implication for Intervention - Magnusson, Kris C.; Redekopp, Dave E. (Canadian Journal of Counselling and Psychotherapy, 1992)
The increasing frequency of occupational change underscores the need for people to become adaptable in their career development. Traditional emphases on skill-building or competence in transition-assistance programs are argued to be insufficient in assisting individuals with transitions, and a process of transition adaptability that emphasizes self-management strategies and salience in addition to competence is presented. Implications for transition interventions and pre-intervention assessment are also discussed.